A survey study of Chinese adolescents’ mental and interpersonal quality: Evidence from COVID-19 pandemic - Huang, Leping; Zhu, Yingfu; Kang, Wei; Zhu, Chunmu (Frontiers in Psychology, 2022)
Within COVID-19 pandemic, social distancing measures and mandatory lockdown are intended to minimize social mobility, they have exerted remarkable impact on individuals’ mental health. The mental health problems caused include fear, anxiety, sense of isolation and development of more maladaptive behaviors due to prolonged lockdown and restricted interpersonal contact. This study aims to disucss a new sight of the mental health quality of Chinese adolescents during the COVID-19 Pandemic in terms of adaptation and interpersonal quality . The study is based on a survey on a total of 7,318 junior and senior high school students aged 12-18 years in various regions of China, and intended to examine the differences in adolescent mental health quality by sociodemographic variables such as gender, grade, urban and rural areas, only child, and parental education level. Our study finds that Chinese adolescents show an overall good adaptation and interpersonal quality during the lockdown. However there exists disparity across different categories in developmental patterns of adaptation and interpersonal quality. In addition, good family environment, moderate financial and emotional support, higher parental education level, etc. contribute to the cultivation and improvement of adolescents’ mental health quality. Finally, we suggest that the government and researchers should pay more attention to adolescents’ mental health issues in terms of adaptability and interpersonal relationships during the COVID-19 pandemic, especially for disadvantaged social groups such as girls, younger students, and low-income family students.